Validity of Dietary Assessment Methods When Compared to the Method of Doubly Labeled Water: A Systematic Review in Adults - Burrows, Tracy L.; Ho, Yan Yee; Rollo, Megan E.; Collins, Clare E. (Frontiers in Endocrinology, 2019)
Accuracy in quantifying energy intake (EI) using common dietary assessment methods is crucial for interpreting the relationship between diet and chronic disease. The aim of this systematic review was to evaluate the validity of dietary assessment methods used to estimate the EI of adults in comparison to total energy expenditure (TEE) measured by doubly labeled water (DLW). Articles in English across nine electronic databases, published between 1973 and February 2019 were retrieved. Studies were included if participants were adults (≥18 years) and used the DLW technique to measure TEE compared to self-reported EI. A total of 59 studies were included, with a total of 6,298 free living adults and a mean of 107 participants per study. The majority of studies including 16 studies that included a technology based method reported significant (P < 0.05) under-reporting of EI when compared to TEE, with few over-reporting EI. Misreporting was more frequent among females compared to males within recall based dietary assessment methods. The degree of under-reporting was highly variable within studies using the same method, with 24 h recalls having less variation and degree of under-reporting compared to other methods.